Kompetensi Kepribadian Pendidik di Madrasah Aliyah Negeri - Saiful Akhyar Lubis; Syamsu Nahar; Nurkholidah Nurkholidah; Rahmadi Ali (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This research was conducted at Madrasah Aliyah Negeri 1 Medan with the aim of knowing the personality competence of educators. This research is a field research and the research approach used is a descriptive qualitative research approach. So this research procedure, will produce descriptive data, in the form of written or spoken words from people and observable behavior. This qualitative descriptive study aims to detect a state or phenomenon as it is. The results of this study will reveal the competence of educators in MAN 1 Medan which is supported by Government Regulation No. 19 of 2005 concerning National Education Standards, which states that teacher personality competencies are personality abilities that are: (1) steady; (2) stable; (3) adults; (4) wise and prudent; (5) authoritative; (6) have a noble character; (7) become role models for students and society; (8) evaluating own performance; and (9) develop themselves continuously, including: 1) Educators at Madrasah Aliyah Negeri 1 Medan have a Steady and Stable personality, 2) Educators at Madrasah Aliyah Negeri 1 Medan have adult and Arif personalities, 3) Educators at Madrasah Aliyah Negeri 1 Medan have personality with noble character, 4) Educators at Madrasah Aliyah Negeri 1 Medan have a dignified personality.Â